Non-Enzymatic Glycation and Formation of Advanced Glycation End-Products Alters the Activity and Related Kinetic Properties of Aldose Reductase - Mkhombo, M.H.; Mogale, M.A.; Shai, L.J.; Lebelo, S.L. (Asian Journal of Chemistry, 2021)
Aldose reductase was incubated with and without either fructose or glucose for 42 days to initiate the glycation process. The concentrations of fructosamine were measured on every 7th day using the standard nitroblue tetrazolium reagent assay. Carboxymethyllysine formed was determined using enzyme linked immunosorbent assay-based methods, fluorescent end-products were measured using spectrofluorometric methods. Activities were assayed by measuring the absorbance of co-factor nicotinamide adenine dinucleotide phosphate hydrogen at 340 nm. Fructosamine, carboxymethyllysine protein adducts and fluorescent end-products were significantly higher (p < 0.001) when aldose reductase was incubated with fructose or glucose than without. Although the glycation of aldose reductase did not result in the alteration of both the optimum pH and temperature of the enzyme, both the activity and Vmax were increased, whereas Km was decreased. Non-enzymatic glycation of aldose reductase increases both its activity and Vmax, while decreasing its Km. Additionally, glycation did not affect the pH of enzyme and temperature optima.